The Impact Of Wholesale Pricing Strategies On The Implementation Of Price Conformance Guarantees By Retailers: A Qualitative Review From A Supply Chain Perspective - Muhammad Rizal; Ruslaini Ruslaini; Yessica Amelia (LPPM STIE Kasih Bangsa, 2024)
This study examines the impact of wholesale pricing strategies on the implementation of Price Matching Guarantees (PMGs) by retailers within the supply chain context. While PMGs serve as tools to enhance consumer attraction and loyalty, their implementation is influenced by the pricing policies set by manufacturers. Through an in-depth literature review, this research finds that discriminatory wholesale pricing strategies hinder retailers from offering PMGs, negatively affecting consumer satisfaction and market competitiveness. Conversely, when wholesale pricing is uniform, PMGs can function more effectively, even if manufacturers oppose such practices. This study suggests the need for increased transparency and collaboration between manufacturers and retailers to create a fairer and more sustainable market environment. The findings provide insights for policymakers to formulate regulations that support more ethical pricing practices and for retailers to optimize their pricing strategies to meet consumer expectations.